Innovative filters made of polyoxadiazole fibers for industrial gas and dust emissions treatment - Lesya V Pelyk; Volodymyr O Vasylechko; Petro O Kutsyk; Yuliya A Peleh (Adsorption Science & Technology)
Practicability of modern high thermal resistant polyoxadiazole fibers in the production of filtration textile materials for gas treatment stations is shown. Thermogravimetric researches proved high thermal resistance (up to 400℃) of filtration materials based on arselone fiber in thermal-oxidative atmosphere. Chemical composition of gas–dust, detained by textile bag filters on gas treatment stations of ferro-alloy plants, is examined. Efficiency of arselone textile material is analyzed in order to extract compounds of Cd, Pb, Mn, Zn, Cu, Cr, Al, Fe, Ca, and Mg from gas–dust.